2002
DOI: 10.1021/je020159m
|View full text |Cite
|
Sign up to set email alerts
|

Excess Enthalpies of the Ternary Mixtures:  Tetrahydrofuran + (Hexane or Cyclohexane) + Decane at 298.15 K

Abstract: Excess molar enthalpies, measured at 298.15 K in a flow microcalorimeter, are reported for tetrahydrofuran + hexane + decane and for tetrahydrofuran + cyclohexane + decane. Smooth representations of the results are described and used to construct constant excess molar enthalpy contours on Roozeboom diagrams. The latter are compared with diagrams obtained when the model of Liebermann and Fried is used to estimate the excess molar enthalpies of the ternary mixtures from the physical properties of the components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The Redlich-Kister smoothing function [5,6], it was found that the LiebermannFried model [7,8], can be useful in representing the excess enthalpies of binary mixtures, and also has the potential for estimating the vapour-liquid equilibria of mixtures and the excess enthalpies of ternary mixtures, from data for the pure components and their binary mixtures. This approach was useful in the recent consideration of (1HX + n-alkane) mixtures [1]. It is therefore of interest to examine how well the Liebermann-Fried model can represent the results for the present systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Redlich-Kister smoothing function [5,6], it was found that the LiebermannFried model [7,8], can be useful in representing the excess enthalpies of binary mixtures, and also has the potential for estimating the vapour-liquid equilibria of mixtures and the excess enthalpies of ternary mixtures, from data for the pure components and their binary mixtures. This approach was useful in the recent consideration of (1HX + n-alkane) mixtures [1]. It is therefore of interest to examine how well the Liebermann-Fried model can represent the results for the present systems.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported excess molar enthalpies at T ¼ 298:15 K, for binary mixtures of 1-hexene (1HX) with a series of n-alkanes [1]. As a continuation of that study we have made similar measurements for binary mixtures of 1HX with the branched alkanes: 2-methylpentane (2MP), 3-methylpentane (3MP), 2,2-dimethylbutane (22DMB), 2,3-dimethylbutane (23DMB), and 2,2,4-trimethylpentane (TMP).…”
Section: Introductionmentioning
confidence: 99%
“…An analogue of MOF‐5 incorporating mesaconic acid was also reported . Despite this scarce use in MOF chemistry, mesaconic acid can be considered a promising organic building block for the green synthesis of MOFs, especially since a biosynthetic pathway for its production from glutamate in water was already described …”
Section: Introductionmentioning
confidence: 99%
“…; ○, Conti et al; gray dash, Erva; -, Matous et al; ◆, Arm et al. ; ◇, Keller et al; gray triangle, Wang et al; − , Inglese et al; ·, Castro et al; gray star, this work; gray circle, Wang et al; ▵, Wang et al. ; gray plus, Biros et al The points used to calculate H int in Table are joined by gray lines.…”
Section: Resultsmentioning
confidence: 85%